Cell phone-based mobile RFID: models, mechanisms and its security. (3rd January 2012) - Park, Namje
Mobile Radio Frequency Identification (RFID) is a newly emerging technology which uses the mobile phone as an RFID reader with a wireless technology and provides new valuable services to the user by integrating RFID and ubiquitous sensor network infrastructure with mobile communication and wireless internet. The mobile RFID enables business to provide new services to mobile customers by securing services and transactions from the end-user to a company's existing e-commerce and IT systems. In this paper, we will discuss mobile RFID technology. We begin with a discussion of the details of a mobile RFID system anatomy, followed by a discussion of the components that make up a typical mobile RFID system framework and the underlying sub-systems that make them work.